Un-Tainting Ars Erotica: The Orient’s Perspective - Roy, Kirti (Universitas Andalas, 2024)
This study examines the evolution of the Kama Sutra within the context of Hinduism and its subsequent misrepresentation through colonial interpretations, particularly focusing on the impact of Western scholar Sir Richard Francis Burton. Within Hinduism, the concept of Purusarthas encapsulates the foundational pursuits of human existence: Dharma, Artha, Kama, and Moksha. While Dharma, Artha, and Moksha have historically held elevated positions, Kama's significance has been marginalized over time. Originally an autonomous pillar akin to the other three, Kama underwent censorship and degradation, notably evidenced in the Manu Shastra, attributing its decline to a deviation from righteous living. The translation of the Kama Sutra into English by Burton in the 19th century propelled its misinterpretation globally, transforming it from a comprehensive guide celebrating love and fulfilment to a sensationalized sex manual. This shift obscured the text's spiritual essence and cultural context, perpetuating Orientalist stereotypes and reinforcing Western sexual fantasies. Burton's translation, influenced by colonial agendas, not only erased the agency of women but also distorted the original intentions of the text, presenting a skewed narrative that catered to Victorian ideals and patriarchal norms. This paper examines the translation, portrayal through the lens of Orientalism, and the intricate gender dynamics the Kama Sutra embodies. Employing critical frameworks of translation theory, feminist analysis, and postcolonial perspectives, this study reveals how the Kama Sutra, as a historical and sexual text, underwent transformation under the influence of Western cultural impositions. Through the prism of translation theory, the paper unravels the colonial lens shaping the Western interpretation, thereby altering the original text to fit Eurocentric ideals. The feminist analysis exposes the erasure of female agency within the text, reinforcing patriarchal norms rather than liberating women. This analysis engages post-colonial theories, notably Edward Said's Orientalism, to illuminate the intricate power dynamics entrenched in the colonial interaction. It exposes how the Western perspective imposed its cultural prism upon Eastern texts, perpetuating a dichotomy between the Occident and the Orient. This division rendered the East a subject of both fascination and apprehension, leading to a reductive depiction that obscured the multifaceted and nuanced tapestry of Eastern cultures. Additionally, the paper integrates feminist and post-colonial theories to comprehensively investigate the profound impact of this representation.